Urbanisation and labour markets in developing countries - Sinclair, Stuart W. (London : Croom Helm, 1978)
This book examines the rural - urban shift in relation to labour markets opportunities with emphasis to developing countries.
Includes bibliographical references and index.
asm 18/02/2019
Loans
Keywords: Labor supply; Cities and towns--Growth; Rural-urban migration; Cities and towns; Urban economics; Developing countries; Africa; Southeast Asia